Cognitive interviewing practice / edited by Debbie Collins. - Collins, Debbie (SAGE, 2015)
Drawing on the approach used at the NatCen Social Research, this book provides practical, hands-on guidance for implementing cognitive interviewing methods in the context of applied social policy research.